2014
DOI: 10.1111/rda.12396
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Freeze‐Drying Technology to Preserve Domestic Animals Sperm

Abstract: ContentsIn recent years, there has been an increased interest in new preservation techniques that facilitate sperm storage and distribution, with freeze-drying (FD) having been proposed as an alternative method for sperm preservation and maintenance of genetic resources in different animal species. FD is a method in which frozen material is dried by sublimation of ice, thereby involving a direct transition from a solid (ice) to a vapour (gas) phase. One of the main advantages of FD is that nitrogen and dry ice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 79 publications
0
30
0
Order By: Relevance
“…Rehydration is the process used to restore the lyophilized product to its original formulation. Freeze‐dried sperm are normally rehydrated by adding pure water, the volume of which should be the same as the original volume of the sperm suspension before FD (Gil et al., ). It is known that the DNA damage is induced by mechanical or oxidative stress not only during FD but also during the holding period before ICSI after rehydration (Kusakabe et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Rehydration is the process used to restore the lyophilized product to its original formulation. Freeze‐dried sperm are normally rehydrated by adding pure water, the volume of which should be the same as the original volume of the sperm suspension before FD (Gil et al., ). It is known that the DNA damage is induced by mechanical or oxidative stress not only during FD but also during the holding period before ICSI after rehydration (Kusakabe et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…It is also well known that stallion semen cooling affects routine sperm quality parameters and pregnancy rates (Brinkerhoff et al, ; Foster et al, ; Heckenbichler, Deichsel, Peters, & Aurich, ; Henderson, Capewell, & Johnson, ; Kiser et al, ; Love et al, ; Urbano et al, ), mostly attributable to the relatively short longevity of cooled‐stored semen of approximately 24–48 hr. Other studies have shown that semen cooling increases SDF values after 48 hr of storage (Blottner et al, ; Fraser, Strzezek, & Kordan, ; Gil et al, ; Linfor & Meyers, ; Love & Kenney, ; Love et al, ; Ortiz et al, ).…”
Section: Introductionmentioning
confidence: 92%
“…It is also well known that stallion semen cooling affects routine sperm quality parameters and pregnancy rates (Brinkerhoff et al, 2010;Foster et al, 2011;Heckenbichler, Deichsel, Peters, & Aurich, 2011;Henderson, Capewell, & Johnson, 1998;Kiser et al, 2013;Love et al, 2015;Urbano et al, 2013), mostly attributable to the relatively short longevity of cooled-stored semen of approximately 24-48 hr. Other studies have shown that semen cooling increases SDF values after 48 hr of storage (Blottner et al, 2001;Fraser, Strzezek, & Kordan, 2011;Gil et al, 2014;Linfor & Meyers, 2002;Love & Kenney, 1998;Love et al, 2015;Ortiz et al, 2017). SDF can be evaluated as a static or dynamic parameter, static assessment involves measuring SDF at one time point whereas dynamic assessment involves evaluating the SDF at multiple time points over a period of incubation at a temperature that mimics the female reproductive tract (usually 37°C).…”
mentioning
confidence: 99%
“…96 There are also many underexplored options in terms of the drying modality and many processing considerations that can be optimized, including establishing the optimal moisture content to minimize degradation during storage and developing storage systems to maintain these levels. 103,104 Optimization of drying and rehydration media and postinjection culture conditions can also lead to increased success rates. 78,81,87,88,96 Initial attempts to optimize drying media have mainly focused on sugars, with successes reported with Trehalose and 3-O-methyl-d-glucose, but there are many other natural protectants that can be evaluated in future studies, including the late embryogenic abundant proteins and many other compatible osmolytes that occur naturally in desiccationtolerant organisms.…”
Section: Dry Preservation Of Nonrodent Spermatozoamentioning
confidence: 99%